EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION DENGAN SCAFFOLDING BERBASIS MODUL PADA MATERI GEOMETRIDIMENSI TIGA DITINJAUDARI KEMANDIRIAN BELAJAR SISWA SMK KELAS XI DI KABUPATEN SRAGEN - Hartono, Hartono; Riyadi, Riyadi; Sujadi, Imam (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The purposes of this research were to investigate: (1) which learning models of Team Assisted Individualization learning model with scaffolding based on module (TAI-S), Team Assisted Individualization learning model (TAI), or direct learning model (DL) results in a better learning achievement in the material of three-dimensional geometry; (2) which independence category of student learning, high, medium or low results in a better learning achievement on the material of three-dimensional geometry; (3) in each category of student learning independence, which learning models of the TAI-S, TAI, or DL model results in better learning achievement on the material of three-dimensional geometry. This research used the quasi experimental method with the factorial design of 3x3. Its population was all the students in Grade XI of Vocational High Schools in Sragen regency. The samples of the research were taken by using the stratified random sampling technique. The data of the research were gathered through documentation, questionnaire, and test. The documentation was employed to investigate the scores of semester test in Mathematics of the students in Semester 1, Academic Year 2012/2013, and was used for balance test among the classes exposed to the TAI-S, TAI, and DL models. The questionnaire was used to find out the independence category of student learning. The test was used to know the students learning achievement in Mathematics with material of three-dimensional geometry. The data of the research were analyzed by using the unbalanced two-way analysis of variance at the significance level of 5%. The results of the research are as follows: (1) the TAI-S learning model result in a better learning achievement than both the TAI and DL models. There are no any differences in the learning achievement of the students with the TAI learning model and DL model. (2) the students with the high independence category result in better learning achievement than students with medium and low independence category. The students with medium independence category result in better learning achievement than students in low independence category (3) in each category of student learning independence, based on the material of three-dimensional geometry, the TAI-S learning model, TAI learning model and DL model do not have correlation between one and another.Keywords : TAI-S learning model, TAI learning model, DL learning. Three Dimensional Geometry, Learning Independence.